The Use and Limitations of Exome Capture to Detect Novel Variation in the Hexaploid Wheat Genome - Burridge, Amanda J.; Winfield, Mark O.; Wilkinson, Paul A.; Przewieslik-Allen, Alexandra M.; Edwards, Keith J.; Barker, Gary L. A. (Frontiers in Plant Science, 2022)
The bread wheat (Triticum aestivum) pangenome is a patchwork of variable regions that includes translocations and introgressions from progenitors and wild relatives. Although a large number of these have been documented, it is likely that many more remain unknown. To map these variable regions and make them more traceable in breeding programmes, wheat accessions need to be genotyped or sequenced. The wheat genome is large and complex and consequently sequencing efforts are often targeted through exome capture. In this study, we employed exome capture prior to sequencing 12 wheat varieties;10 elite T. aestivum cultivars and two T. aestivum landrace accessions. Sequence coverage across chromosomes was greater towards distal regions of chromosome arms and lower in centromeric regions, reflecting the capture probe distribution which itself is determined by the known telomere to centromere gene gradient. Superimposed on this general pattern, numerous drops in sequence coverage were observed. Several of these corresponded with reported introgressions. Other drops in coverage could not be readily explained and may point to introgressions that haven't, to date, been documented.